2019
DOI: 10.1080/24750573.2019.1595867
|View full text |Cite
|
Sign up to set email alerts
|

Social functioning and its association with accompanying psychiatric symptoms in adolescents with anorexia nervosa

Abstract: OBJECTIVE: This study aimed to investigate social functioning and its relation to associated psychiatric symptoms and disorders in adolescent girls with anorexia nervosa. METHODS: Thirty-two adolescent girls with anorexia nervosa aged between 12 and 18 years were compared to a control group of 30 adolescent girls without any psychiatric disorder. The Schedule for Affective Disorders and Schizophrenia for School-Age Children, Present and Lifetime Version (K-SADS-PL) was applied to determine comorbid psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Adolescents with anorexia nervosa report submissive behaviors, unfavorable social comparison, sensitivity to rejection and poorer quality of social relationships to a greater extent than their healthy peers (Cardi et al, 2019 ; Kalaycı et al, 2019 ; Rowlands et al, 2021 ). Some of these problems, for example greater alienation perceived within family and peer relationships (Pelletier Brochu et al, 2018 ) and heightened interpersonal sensitivity (Rowlands et al, 2021 ), have been associated with a greater severity of self‐reported eating disorder psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with anorexia nervosa report submissive behaviors, unfavorable social comparison, sensitivity to rejection and poorer quality of social relationships to a greater extent than their healthy peers (Cardi et al, 2019 ; Kalaycı et al, 2019 ; Rowlands et al, 2021 ). Some of these problems, for example greater alienation perceived within family and peer relationships (Pelletier Brochu et al, 2018 ) and heightened interpersonal sensitivity (Rowlands et al, 2021 ), have been associated with a greater severity of self‐reported eating disorder psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the included studies employed a cross‐sectional design ( N = 13; 76.47%) (Ambwani et al, 2016; Blomquist et al, 2012; Brugnera, Coco, Salerno, et al, 2018; Brugnera, Coco, Tasca, et al, 2018; Cardi et al, 2014; Cardi et al, 2018; Connan et al, 2007; De Paoli et al, 2017; Duarte et al, 2016; Kalayci et al, 2019; Pinto‐Gouveia et al, 2014; Troop et al, 2003, 2014). Three studies (17.64%) utilized a prospective cohort study design (Brugnera et al, 2019; Carter et al, 2012; Hartmann et al, 2010), whereas one study (6.25%) (Ma & Kelly, 2020) employed ecological momentary assessment (EMA), which assessed participants repeatedly in their natural environment in real time.…”
Section: Resultsmentioning
confidence: 99%
“…For the prospective cohort studies, two did not report the length of time between baseline data collection and follow‐up, but only described it as pre‐ and posttreatment (Carter et al, 2012; Hartmann et al, 2010), whereas in the other study (Brugnera et al, 2019), the length of time between baseline data collection and follow‐up was 12 months. The majority of studies ( N = 12; 70.58%) included a control group of healthy participants (i.e., not having a diagnosis of ED) (Ambwani et al, 2016; Brugnera, Coco, Salerno, et al, 2018; Brugnera, Coco, Tasca, et al, 2018; Brugnera et al, 2019; Cardi et al, 2014; Carter et al, 2012; Connan et al, 2007; De Paoli et al, 2017; Hartmann et al, 2010; Kalayci et al, 2019; Pinto‐Gouveia et al, 2014; Troop et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations